2014
DOI: 10.1177/1098612x14532089
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral treatment of feline immunodeficiency virus-infected cats with (R)-9-(2-phosphonylmethoxypropyl)-2,6-diaminopurine

Abstract: Feline immunodeficiency virus (FIV), the causative agent of an acquired immunodeficiency syndrome in cats (feline AIDS), is a ubiquitous health threat to the domestic and feral cat population, also triggering disease in wild animals. No registered antiviral compounds are currently available to treat FIV-infected cats. Several human antiviral drugs have been used experimentally in cats, but not without the development of serious adverse effects. Here we report on the treatment of six naturally FIV-infected cats… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
7
0
1
Order By: Relevance
“…In particular, male neutered cats were overrepresented in the FIV-infected group, which is similar to other reports. [55][56][57] However, no effect of age or sex on sCysC could be observed in a recent study by our group. The effect of age and sex on uCysC has not yet been evaluated.…”
Section: Discussionmentioning
confidence: 82%
“…In particular, male neutered cats were overrepresented in the FIV-infected group, which is similar to other reports. [55][56][57] However, no effect of age or sex on sCysC could be observed in a recent study by our group. The effect of age and sex on uCysC has not yet been evaluated.…”
Section: Discussionmentioning
confidence: 82%
“…Among the many achievements, these efforts led to approval of an effective FIV vaccine in 2002. Recent studies have addressed important issues such as mechanisms of FIV transmission, replication and evolution [ 22 , 23 , 24 , 25 , 26 , 27 ], FIV vaccine efficacy [ 28 , 29 ], the role of neutralizing antibodies in disease progression [ 28 , 30 , 31 ], virus assembly and release [ 32 , 33 ], viral latency and eradication strategies [ 34 , 35 , 36 ], development of adjunctive therapies [ 37 , 38 , 39 , 40 ], immunology [ 41 , 42 , 43 , 44 , 45 ], interactions with the microbiome [ 46 , 47 ], development of antiretroviral compounds [ 48 , 49 , 50 ] and development of protocols for assessing feline cognitive function [ 51 , 52 , 53 , 54 ]. Many of these efforts are summarized in this volume and in a review by Bienzle [ 55 ].…”
Section: Fiv Infection Of the Nervous Systemmentioning
confidence: 99%
“…It is also strongly active against animal retroviruses, especially feline immunodeficiency virus. Although strong conclusions cannot still be done, some studies revealed slightly positive ( Vahlenkamp et al, 1995 ; Taffin et al, 2015 ). It is clear that the activity of ( R )-PMPDAP in vivo warrants further investigations including synthesis of prodrugs ( Krečmerová et al, 2013 ).…”
Section: Acyclic Nucleoside Phosphonates (Anps)mentioning
confidence: 99%